A Randomized Controlled Trial on the Effectiveness of Tramadol as an Adjunct to Bupivacaine for Caudal Analgesia in Children - Fazal Wadood, Muhammad Naeem, Hafiz Imran Ul Haq, Robina Bangash, Amber Amer, Varda Balouch, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The purpose of analgesia in postoperative period is to minimize pain with the fewest probable side effects and to obtain the highest possible cost-effectiveness in our environment. In children, caudal anesthesia is often given in combination with general anesthesia for postoperative and intraoperative anesthesia. To extend the length of anesthesia; adjuvants can be further added to local anaesthetics. This research was performed to determine the caudal bupivacaine anesthesia duration given in combination with tramadol. Study Design: A prospective, comparative, randomized, double-blinded study Place and duration: In the department of Anesthesia, Khyber Teaching Hospital, Peshawar for one-year duration from 21st January 2021 to 20th January 2022. METHODS: 80 patients, 3-8 years of age, enduring elective urological, lower limb and lower abdominal surgery. Patients were randomised in to group A (n = 40) given 0.25% bupivacaine 1 ml / kg and group B (n = 40) receiving bupivacaine 0.25% in dose of 1 ml / kg plus 1 mg / kg tramadol. The hemodynamic responses, side effects and analgesia total duration were observed and analyzed. Results: The patients were comparable in groups A and B in terms of hemodynamic response and demographics and were not significant statistically (p greater than 0.05). It was detected that the analgesia mean time was longer significantly in B group (464.2 ± 167.1 minutes vs 238.1 ± 71.5 minutes, P <0.001). The postoperative vomiting was perceived in two cases, one in each group. Conclusions: One mg / kg Tramadol adjuvant to 0.25% bupivacaine for caudal anesthesia in children effectively lengthens the analgesia duration deprived of increasing side effects. Keywords: bupivacaine; tramadol and caudal analgesia.